Implementasi Kebijakan Pembatasan Kegiatan Masyarakat Pada Ruang Publik Terbuka Dalam Penanggulangan Wabah Covid-19 Di DKI Jakarta - Yoka Mai Patria (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
This research is a qualitative descriptive study using descriptive analysis by describing the implementation of community activity restriction policies (PKM) in DKI Jakarta. The results of this study indicate that there is an adaptation of the physical elements of public spaces in Jakarta, such as the addition of simple cleaning facilities to comply with health protocols. Based on observations and analysis, the adaptation that occurs does not have to be an adaptation of physical elements. However, it can also only be in the form of maintaining distance, the need for larger road spaces, choosing seats, or the purpose of using public spaces to increase immunity and health due to quarantine during the pandemic. This adaptation is supported by written regulations for the use of public spaces and must be obeyed by visitors.